THE PHYSIOLOGICAL RESPONSE AND PRODUCTIVITY OF MAIZE (Zea mays L.) ‘Sweet Boy-02’ IN DIFFERENT LIGHT AND WATER TREATMENT - Hafidha Asni Akmalia; E. Suharyanto (Jurnal Teknosains, 2017)
Physiological response is one of adaptation in plant toward its environment. This is related to plant productivity because there is a different physiological mechanism playing an important role in phenotype and productivity. The aims of the research were (1) to evaluate physiological response of maize in different light and water treatment, and (2) to determine the right light and water treatment to increase maize productivity. This research used Randomized Completed Design with 3 regimes of light intensity (63694, 11408 dan 3897 Lux) and 3 regimes of watering (2 L/ 1,6 L/ and 1,2 L). Each combination was done with 3 replications. Maize was harvested in 75 days after the treatment and the measured physiological responses were chlorophyll content, proline content, and root length meanwhile the plant productivity was seen from the fruit. Data were analyzed by Anava and DMRT test with significance level of 5%. The results showed that the light intensity L1 (63694 Lux) and watering W1 (2 L) increased the chlorophyll content, and produvtivity while proline content and root length increased under high light intensity L1 (63694 Lux) and drought W2 (1,6 L)-W3 (1,2 L). The optimal productivity presented in treatment L1 (63694 Lux) and W1 (2 L) seen from the heaviest fruit.